heredERA Breast Cancer: a phase III, randomized, open-label study evaluating the efficacy and safety of giredestrant plus the fixed-dose combination of pertuzumab and trastuzumab for subcutaneous injection in patients with previously untreated HER2-positive, estrogen receptor-positive locally advanced or metastatic breast cancer - Sherko Kuemmel; Catherine Harper-Wynne; Yeon Hee Park; Fábio Franke; Michelino de Laurentiis; Eva Schumacher-Wulf; Daniel Eiger; Sarah Heeson; Andrés Cardona; Özgür Özyilkan; Flavia Morales-Vàsquez; Ciara Metcalfe; et al. (BMC Cancer, 2024)
Abstract Background HER2-positive, estrogen receptor-positive breast cancer (HER2+, ER+ BC) is a distinct disease subtype associated with inferior response to chemotherapy plus HER2-targeted therapy compared with HER2+, ER-negative BC. Bi-directional crosstalk leads to cooperation of the HER2 and ER pathways that may drive treatment resistance; thus, simultaneous co-targeting may optimize treatment impact and survival outcomes in patients with HER2+, ER+ BC. First-line (1L) treatment for patients with HER2+ metastatic BC (mBC) is pertuzumab, trastuzumab, and taxane chemotherapy. In clinical practice, dual HER2 blockade plus a fixed number of chemotherapy cycles are given as induction therapy to maximize tumor response, with subsequent HER2-targeted maintenance treatment given as a more tolerable regimen for long-term disease control. For patients whose tumors co-express ER, maintenance endocrine therapy (ET) can be added, but uptake varies due to lack of data from randomized clinical trials investigating the superiority of maintenance ET plus dual HER2 blockade versus dual HER2 blockade alone. Giredestrant, a novel oral selective ER antagonist and degrader, shows promising clinical activity and manageable safety across phase I–II trials of patients with ER+, HER2-negative BC, with therapeutic potential in those with HER2 co-expression. Methods This phase III, randomized, open-label, two-arm study aims to recruit 812 patients with HER2+, ER+  locally advanced (LA)/mBC into the induction phase (fixed-dose combination of pertuzumab and trastuzumab for subcutaneous injection [PH FDC SC] plus a taxane) to enable 730 patients to be randomized 1:1 to the maintenance phase (giredestrant plus PH FDC SC or PH FDC SC [plus optional ET]), stratified by disease site (visceral versus non-visceral), type of LA/metastatic presentation (de novo versus recurrent), best overall response to induction therapy (partial/complete response versus stable disease), and intent to give ET (yes versus no). The primary endpoint is investigator-assessed progression-free survival. Secondary endpoints include overall survival, objective response rate, clinical benefit rate, duration of response, safety, and patient-reported outcomes. Discussion heredERA BC will address whether giredestrant plus dual HER2 blockade is superior to dual HER2 blockade alone, to inform the use of this combination in clinical practice for maintenance 1L treatment of patients with HER2+, ER+ LA/mBC. Trial registration ClinicalTrials.gov, NCT05296798; registered on March 25, 2022. Protocol version 3.0 (November 18, 2022). Sponsor: F. Hoffmann-La Roche Ltd, Grenzacherstrasse 124 4070, Basel, Switzerland.